Impact of Financial Literacy on the Socio-Economic Well-being of People in Kaski District, Nepal - Ranabhat, Deepesh (Economic Journal of Development Issues, 2023)
Financial literacy is considered one of the crucial factors influencing the attainment of the Sustainable Development Goals (SDGs). This paper examines how financial literacy affects social and economic well-being in Nepal’s Kaski District. The study follows descriptive and cross-sectional research designs. A sample of 385 households was selected for data collection. The head of each household was identified as the participant, and a survey questionnaire was used to collect the necessary data. Various statistical techniques, such as frequency distribution, exploratory factor analysis, and structural equation modelling, were used for data analysis. This study found that financial literacy positively influences both the social and economic well-being of households. Possessing the necessary knowledge and skills in financial matters enables individuals to meet their social and economic needs. The findings are very important for policymakers, educators, and stakeholders to enhance financial knowledge and skills and support the achievement of the Sustainable Development Goals.